Band Bending Mechanism in CdO/Arsenene Heterostructure: A Potential Direct Z-scheme Photocatalyst - Ren, Kai; Zheng, Ruxin; Yu, Jin; Sun, Qingyun; Li, Jianping (Frontiers in Chemistry, 2021)
For the few years, two-dimensional (2D) materials have aroused general focus. In order to expand the properties and application range of 2D materials, two different layered materials are usually combined into heterostructure through van der Waals (vdW) interaction. In this research, based on first-principles simulation, we propose CdO/Arsenene (CdO/As) vdW heterostructure as a semiconductor possessing a direct bandgap by 2.179 eV. Besides, the CdO/As vdW heterostructure presents type-II band alignment, which can be used as a remarkable photocatalyst. Importantly, the CdO/As heterostructure demonstrates a direct Z-type principle photocatalyst by exploring the band bending mechanism in the heterostructure. Furthermore, we calculated the light absorption characteristics of CdO/As vdW heterostructure by optical absorption spectrum and conversion efficiency of a novel solar-to-hydrogen efficiency (ηSTH) about 11.67%, which is much higher than that of other 2D photocatalysts. Our work can provide a theoretical guidance for the designing of Z-scheme photocatalyst.